Language for Specific Purposes: A Course Design for PROGEST/CEFET-MG - Kellen S. Batista Marques; Maria Inês Garíglio (The ESPecialist: Research in Language for Specific Purposes, 2011)
This paper reports a course design based upon the language for specific purpose approach in CEFET-MG, for the Programa de Capacitação em Gestão de Obras - PROGEST (Program of Study in Engineering, Society and Technology). It is related to the subject matter Language for Professional Purposes, which provides space for discussion about the use and the importance of language and its variations. Its objective is to demonstrate the interaction between the diverse uses of the language, prioritizing the working environment of the professional pupils enrolled in the course. So, the target public profile, its work market - the Civil Construction, the demanded qualification as well as the influence of reading abilities and literacy on the social-communicational contract expected in such environment are discussed.